Anticipatory Bail and Criminal Justice System in India - Prof. Pradeep Singh (International Journal of Business and Social Science Research, 2020)
Social reputation and personal liberty are two important things in life human beings which are most dear and most respected. Whenever any person has enmity with another person, he tries to affect the social reputation and personal liberty of later person and usually for the purpose criminal justice system is misused. Vested interests file the false case, thereby, the alleged person may be arrested and kept in custody which may cause a loss of reputation and personal liberty of the alleged person. Such misuse of the criminal justice system is a reality. Therefore, it is the responsibility of the criminal justice system itself to protect innocent persons falsely alleged in a criminal case. Indian criminal justice system has prescribed anticipatory bail to protect the falsely alleged person. This article will analyze the legal regime provided in the Indian criminal justice system about anticipatory bail.